The South African police service's response to sexual and gender-based violence: the experience of survivors - Griqua, Erin (Department of Psychology, 2025)
The South African government's attempts to address the scourge of violence against women and children, although laudable in theory, have not materialized as effectively as intended. The shortcomings of the South African Police Service (SAPS) as the first point of contact in the Criminal Justice System have contributed to the failure of the system to respond to sexual and gender-based violence (SGBV) appropriately. The objective of this study was to investigate the experiences of survivors when reporting an incident of SGBV to the South African Police Services. Twelve women were recruited via snowball sampling from the Manenberg SAPS Victim Empowerment Programme and were invited to participate in a 45-60-minute semi-structured interview. Following the research topic, this study employed an intersectional feminist theoretical framework, and a thematic analysis was utilized for the analytical approach. The analysis produced five themes pertaining to the experiences of survivors when reporting an incident of SGBV to SAPS and the meaning-making of these experiences. The themes that emerge from this research include narratives on the inevitability of delayed justice, narratives on the experiences of reporting to the South African Police Services (SAPS), evidence narratives, narratives on the constraints of reporting gender-based violence, and, lastly, empowered narratives. The findings of this study highlight that the South African police's response to SGBV needs to be improved. The study also highlights the importance of and need for victim-centric services at South African police stations for survivors of SGBV.